2023
DOI: 10.3390/buildings13082113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Measured CO2 Levels through Long-Term Monitoring in Renovated Multifamily Buildings: A Common Case

Ancuța Maria Măgurean,
Horia Alexandru Petran

Abstract: The purpose of this study was to analyze the indoor air quality, in particular, the CO2 level, in a real environment, within 16 apartments located in the municipality of Zalău, Romania, in five recently renovated multifamily buildings in which families live under normal conditions. Long-term monitoring was undertaken for 4.5 months, during the heating season of 2022–2023. A representative microclimate perspective was analyzed: the median value of the time fraction, which exceeded the Indoor Environment Quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The obtained results showed small differences between ventilation system in terms of human thermal comfort in rooms with low thermal inertia, but indicated energy and economic efficiency of the passive ventilation system. In turn, Măgurean and Petran [24] analysed the indoor environment in sixteen apartments located in Romania in five recently renovated multi-family buildings. Even if the thermal comfort conditions in the rooms increased after modernisation, it was found that almost half of the time the bedrooms had poor indoor air quality due to inadequate ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed small differences between ventilation system in terms of human thermal comfort in rooms with low thermal inertia, but indicated energy and economic efficiency of the passive ventilation system. In turn, Măgurean and Petran [24] analysed the indoor environment in sixteen apartments located in Romania in five recently renovated multi-family buildings. Even if the thermal comfort conditions in the rooms increased after modernisation, it was found that almost half of the time the bedrooms had poor indoor air quality due to inadequate ventilation.…”
Section: Introductionmentioning
confidence: 99%